Spectrophotometric Determination of Domperidone in its Pharmaceutical Formulation Through Charge Transfer Complexation Reactions - A. Alarfaj, Nawal; A. Mostafa, Azza; A. Al-Ghamdi, Zinah (Asian Journal of Chemistry, 2013)
Two simple, precise and accurate spectrophotometric methods have been developed for determination of domperidone in bulk drug and in its pharmaceutical formulation. The methods are based on the formation of charge-transfer complex between domperidone as p-donor and a p-acceptor like 2,3-dichloro-5,6-dicyano-l,4-benzoquinone in method (1) or a s-acceptor like iodine in method (2). The products exhibit absorption maxima at 458 nm in acetonitrile for method (1) and at 394 nm in chloroform for method (2), respectively. Under the optimum reaction conditions, linear relationships with good correlation coefficients (0.9999 for both methods) were found between the absorbance and the concentration of domperidone in the range of 10-70 μg/mL in both methods. The limit of detection values are found to be 1.26 and 1.14 μg/mL for method (1) and method (2), respectively, with corresponding limit of quantification values of 4.20 and 3.80 μg/mL. The stoichiometry of the reaction was found to be 1:1 in both methods. The proposed methods were applied successfully for the determination of domperidone in motilium tablets with good accuracy and precision. The results obtained by the proposed methods were compared favorably with those of the reference method.